ANALISIS FAKTOR YANG MENYEBABKAN RENDAHNYA KUNJUNGAN PASIEN RAWAT JALAN DI RSUD dr. FAUZIAH BIREUEN TAHUN 2021 - Darlina Darlina; Fithri Handayani Lubis (Jurnal Kajian Kesehatan Masyarakat, 2022)
Hospitals need to improve strategies to be able to increase outpatient satisfaction so that patients will make decisions to make repeat visits and have an impact on increasing the number of outpatient visits. The type of research used is quantitative research using a cross-sectional approach or research that aims to analyze the factors that cause low outpatient visits at dr. Fauziah Bireuen in 2021. Held at the dr. Fauziah Bireuen, from November 2021 to March 2022. The sample size is calculated by using the minimum sample formula from Lemeshow, from the calculation, the minimum sample size is 60 people. The sampling technique used is consecutive sampling, The results showed that there was a statistical relationship between registration services, doctor services, pharmacy services and the hospital environment with the low number of outpatient visits at RSUD dr. Fauziah Bireuen and the most dominant variable is the registration service variable and based on the value of Exp(B) on the results of the Multivariate test it is known that the registration service has the largest value of 6.376 so it can be assumed that the registration service has a chance of 6.376 times causing low outpatient visits at RSUD dr. Fauziah Bireuen. The need for adding politeness and friendliness indicators to the SOP for registration services, optimizing the use of electronic medical records (RME) to improve the performance of registration service officers and shorten registration waiting times, increasing the comfort of the pharmacy service waiting room by adding a TV unit, so that patients queuing and waiting for drugs become more comfortable and less bored.